25‐Hydroxyvitamin D Threshold for the Effects of Vitamin D Supplements on Bone Density: Secondary Analysis of a Randomized Controlled Trial. (15th June 2018) - Macdonald, Helen M; Reid, Ian R; Gamble, Gregory D; Fraser, William D; Tang, Jonathan C; Wood, Adrian D
ABSTRACT: Most trials of vitamin D supplementation have shown no benefits on bone mineral density (BMD), although severe vitamin D deficiency causes osteomalacia, which is associated with profound BMD deficits. Recently, the ViDA‐BMD study from New Zealand demonstrated a threshold of baseline 25‐hydroxyvitamin D (25OHD; 30 nmol/L) below which vitamin D supplementation did benefit BMD. We have now reexamined data from a similar trial in Aberdeen to determine whether a baseline 25OHD threshold of 30 nmol/L is also observed in that database. The Aberdeen study recruited 305 postmenopausal women in late winter and randomized them to receive placebo, vitamin D 400 IU/d, or vitamin D 1000 IU/d over 1 year. As previously reported, BMD loss at the hip was reduced by vitamin D 1000 IU/d only, and there was no significant treatment effect of either dose at the lumbar spine. In the present analysis, when the trial participants were grouped according to whether their baseline 25OHD was ≤30 nmol/L or above this threshold, significant treatment effects were apparent at both the spine and hip in those with baseline 25OHD ≤30 nmol/L, but no significant effects were apparent in those with baseline 25OHD above this level. There was evidence of a similar threshold for effects on parathyroid hormone, but no groups showed changes in bone turnover markers during the study. It is concluded that vitamin D supplements only increase bone density in adults with nadir 25OHD ≤30 nmol/L. This moves us further toward a trial‐based definition of vitamin D deficiency in adults with adequate calcium intakes and suggests that supplement use should be targeted accordingly. Future trials of vitamin D supplementation should focus on individuals with 25OHD concentrations in this range. © 2018 American Society for Bone and Mineral Research.